2009
DOI: 10.1111/j.1467-9566.2009.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring stigma: medical knowledge and the stigmatisation of parents of children diagnosed with autism spectrum disorder

Abstract: This paper analyses 12 parent interviews to investigate the stigmatisation of parents of children diagnosed with an autism spectrum disorder. Drawing on poststructural accounts of the relationship between knowledge and subjectivity, the stigma concept is critically interrogated in order to address previous individualistic constructions of stigmatisation and to place stigma within the power dynamics of social control. The results of the study indicate that a child's diagnosis with an autism spectrum disorder (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
2
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(176 citation statements)
references
References 27 publications
7
153
2
14
Order By: Relevance
“…The parental reports illustrated the tendency of some professionals to minimize problems and/or to enhance the feeling of guilt of the parents: (Chamak 2008;Farrugia 2009). The diagnosis provides a degree of explanation for a child"s behavior, and helps parents accept that they are not to blame for the condition (Chamak et al 2011).…”
Section: The Parents Are Often the First To Detect Signs Of Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…The parental reports illustrated the tendency of some professionals to minimize problems and/or to enhance the feeling of guilt of the parents: (Chamak 2008;Farrugia 2009). The diagnosis provides a degree of explanation for a child"s behavior, and helps parents accept that they are not to blame for the condition (Chamak et al 2011).…”
Section: The Parents Are Often the First To Detect Signs Of Concernmentioning
confidence: 99%
“…Autism has shifted from being a rare disease to a broad syndrome and from a psychiatric disorder to a genetic disease involving an atypical development of the nervous system (Bumiller 2009;Hacking 2002;Nadesan 2005;Silverman 2008). Among parents, biological explanations are preferred because they decrease feelings of guilt (Chamak 2008;Farrugia 2009). In the 1960s psychoanalytic discourse constructed autism as the result of "cold" mothering, and the "refrigerator mother" theory diffused through popular psychology.…”
Section: Changes In the Social Construction Of Autism: An Internationmentioning
confidence: 99%
“…al. 2005;Farrugia 2009). Others have been specifically interested in the dynamics of maternal stigmatisation.…”
Section: Theorising Prolonged Dependency: Developmental Disability Anmentioning
confidence: 99%
“…20 Farrugia found that families with autistic children changed their social environment as a result of stigmatization and lost almost half of their friends. 21 In this study, it is thought that the reason for parents isolating themselves may be disapproval/exclusion by their friends. It is important to educate the community in this respect.…”
Section: Discussionmentioning
confidence: 99%